PENGARUH SIKAP BERPERILAKU, NORMA SUBYEKTIF DAN KONTROL PERILAKU PERSEPSIAN PADA MINAT BERWIRAUSAHA - Putra, I Putu Mega Juli Semara; Juniariani, Ni Made Rai (Program Studi Akuntansi Fakultas Ekonomi Universitas Mahasaraswati Denpasar, 2018)
This research aims to determine the effect of attitudes towards behavioral, subjective norms, and perceived behavioral control on entrepreneurship interests. The data used are primary data in the form of answers to questionnaires distributed to students of Accounting Department at Faculty of Economics, PTS sekota Denpasar by using survey method. Selection of sample using slovin formula so that obtained by 337 samples. The research using multiple linear regression analysis. The hypothesis test results are the (1) attitudes towards behavioral have positive effect on entrepreneurship interest (2) subjective norm have positive effect on interest to behave and (3) perceived behavioral control have positive effect on entrepreneur interest.